Progress of p53/p21 pathway and cell cycle arres in acute kidney injury research - LIU Zhuo-liang; LI Ya-feng; LI Rong-shan (Linchuang shenzangbing zazhi)
As one of the most common acute and severe diseases in hospitalized patients, acute kidney injury(AKI) can sharply decrease kidney function. DNA damage exists in the early stages of AKI, and one of the major cellular responses to DNA damage is cell cycle arrest, in which the tumor protein p53 plays an important role. Based on our knowledge of the p53/p21 signaling pathway and DNA damage to date, this review focuses on the role of cell cycle arrest and the p53/p21 signaling pathway in progression of AKI. A better understanding of protective effect of cell cycle arrest, and the mechanisms and function of the p53/p21 signaling pathway will enable the development of therapeutic strategies for treating AKI.